Dr Tatu Kamau vs The Attorney General and Others: problems and prospects in Kenya's 2021 High Court ruling to uphold the Prohibition of Female Genital Mutilation Act 2011 - a reply to 'The prosecution of Dawoodi Bohra women' by Richard Shweder. Issue 1 (February 2022) - Ahmadu, Fuambai Sia; Kamau, Tatu
Abstract : '[The] average third world woman leads an essentially truncated life based on her feminine gender (read: sexually constrained) and being "third world" (read: ignorant, poor, uneducated, tradition-bound, domestic, family-oriented, victimized, etc.). This, I suggest, is in contrast to the (implicit) self-representation of Western women as educated, modern, as having control over their own bodies and sexualities, and the freedom to make their own decisions' (Mohanty, 2003 : 337). Not much has changed regarding Western views of the 'third world woman' in the 37 years since Chandra Mohanty made these remarks – this is especially so when it comes to the heated topic of female circumcision, female genital cutting or what opponents refer to as female genital mutilation among African and Muslim women. In Richard Shweder's (2022) conclusion of the target article, he outlines four key considerations that justify male circumcision and argues that these factors ought to also determine the acceptability of female circumcision in liberal democracies: (1) the practice is broadly supported by the communities that uphold them; (2) the practice is motivated by the fundamental principle of gender equality; (3) the practice is not more physically invasive than what is legally allowed for male circumcision; and (4) there is scant evidence of harm. Shweder (2022) points out that all four conditions are consistent with the practice of khatna – a mild, barely visible form of female circumcision among the Dawoodi Bohra. In this response article, we consider these four standards in our discussion of Kenya's High Court ruling this year to uphold the Prohibition of Female Genital Mutilation Act 2011. It first describes the legal context for challenging the constitutionality of the Act and outlines the key provisions within the Kenyan Constitution and its Bill of Rights that the plaintiff identified in her petition, focusing especially on the rights of Kenyan women to bodily autonomy and cultural expression. It then delves into the complex symbolic, cultural and socio-religious nuances of gender-inclusive circumcision rituals, citing various case studies in our reflection on the four points Shweder proposes for legitimising female circumcision.